2020
DOI: 10.1002/eap.2239
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends indicate that invasive plants are pervasive and increasing in eastern national parks

Abstract: While invasive plant distributions are relatively well known in the eastern United States, temporal changes in species distributions and interactions among species have received little attention. Managers are therefore left to make management decisions without knowing which species pose the greatest threats based on their ability to spread, persist and outcompete other invasive species. To fill this gap, we used the U.S. National Park Service’s Inventory and Monitoring Program data collected from over 1,400 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…For example, there is often no net change on average in local scale species richness in areas that have not undergone substantial land-use change (Dornelas et al, 2014;Vellend et al, 2013). However, when natural vegetation is converted to agriculture, some areas experience declines in species richness (Newbold et al, 2015), while other places experience increases in species richness when non-native species colonizations exceed native species extinctions (Miller et al, 2021;Sax & Gaines, 2003). Disturbances such as forest loss can elevate rates of biodiversity change, but this is true for both losses and gains (Daskalova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is often no net change on average in local scale species richness in areas that have not undergone substantial land-use change (Dornelas et al, 2014;Vellend et al, 2013). However, when natural vegetation is converted to agriculture, some areas experience declines in species richness (Newbold et al, 2015), while other places experience increases in species richness when non-native species colonizations exceed native species extinctions (Miller et al, 2021;Sax & Gaines, 2003). Disturbances such as forest loss can elevate rates of biodiversity change, but this is true for both losses and gains (Daskalova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the parks experiencing the most severe impacts of chronic deer browse also have the highest and increasing invasive plant loads (Fisichelli & Miller, 2018; Miller et al, 2021). In fact, this study consistently found invasive plant cover to be an important and negatively associated predictor of regeneration abundance, particularly for sapling density and the stocking index.…”
Section: Discussionmentioning
confidence: 99%
“…Where overabundant deer and invasive shrubs overlap, canopy gaps often result in conversion to invasive shrub thickets that suppress tree regeneration. In MORR, for example, gaps formed from ash dieback and windthrow events have converted to invasive shrub thickets (Miller et al, 2021). Silvicultural practices that create canopy gaps intended to increase forest resilience by promoting diverse and abundant regeneration must therefore be applied with extreme caution in forests with high deer densities and abundant invasive plants (Webster et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, efforts to control invasive plant species must be planned and implemented with consideration of the direct and subsequent impacts of invasion (D'Antonio and Meyerson, 2002;Barney et al, 2013). The distribution of both M. vimineum and A. petiolata is rapidly expanding across national parks in the eastern US (Miller et al, 2020). Due to this spread and potential impacts to native vegetation, control of these species, particularly M. vimineum, is noted as a management priority.…”
Section: Discussionmentioning
confidence: 99%